Good agronomic practices in cocoa cultivation: rehabilitating cocoa farms - Asare, R.; Afari-Sefa, Victor; Muilerman, Sander; Anim-Kwapong, G.J. (Burleigh Dodds Science Publishing Limited, 2018)
Cocoa cultivation covers a total area of about 5.9 million ha worldwide with around 73% of this area found in the four large cocoa-producing countries in West Africa namely Cameroon, Côte d’Ivoire, Ghana and Nigeria. Adoption of good agronomic practices is crucial for the sustainability of cocoa cultivation and this chapter describes good practices at both the pre- and post-planting stages. The chapter focuses on the challenge of rehabilitating cocoa farms, and includes a detailed case study on rehabilitation of farms in Ghana. The chapter looks forward to future developments in this area and provides further reading on the subject.